Effect of dual stage solid solution on the microstructure and mechanical properties of Al-Zn-Mg-Cu - Zhuo WANG; Yizhe WANG; Jiaxing WANG; Zihan LIU; Junye ZHOU; Ying LIU; Xiao YANG; Liwei WANG (Journal of Hebei University of Science and Technology)
In order to solve the problem of difficult dissolution of second phase particles caused by excessive high Zn content during the traditional heat treatment of Al-Zn-Mg-Cu alloy, the effects of different two-stage solid solution processes on the microstructure and mechanical properties of the as-quenched and T6 aged Al-Zn-Mg-Cu alloy with high Zn content were investigated by using optical microscope (OM), scanning electron microscope (SEM), Vickers hardness tester and tensile testing under room temperature. The results show that with the increase of the first-stage solid solution temperature, the strength and hardness of the alloy increase, and the overall mechanical properties of the materials improve. The elongation rate of the alloy increases firstly and then decreases with the increase of the first-stage solid solution temperature, and the tensile fracture shows toughness fracture. After the alloy subjecting to a two-step solution heat treatment and quenching process at 460 ℃ for 1 h and then at 475 ℃ for 2 h, the tensile strength, yield strength and elongation of the alloy are 580.5 MPa, 465.3 MPa and 13.6%, respectively, indicating good comprehensive mechanical properties. The modulation of the temperature within the first stage of the two-stage solution treatment process is conducive to the amelioration of the comprehensive performance of aluminum alloy materials with a high Zn content. It can provide theoretical reference for improving the heat treatment process of aluminum alloy materials.